Nanotechnology in Amyloid Lateral Sclerosis (ALS) - review - Agata Rocka; Dominika Psiuk; Faustyna Piędel; Klaudia Żak; Agnieszka Brzezińska (Kazimierz Wielki University, 2020)
Introduction and purpose: Amyloid Lateral Sclerosis (ALS) is progressive, cachectic neurodegenerative disease. The lack of effective therapy, which could prevent disease progression and minimize degeneration of motor neurons, contributes to unceasing exploration for novel therapeutic methods. Nanotechnology remains one of the most promising areas among novel agents in neurodegenerative diseases treatment. Recent studies have shown that application of nanoparticles for drug delivery might develop greater effects in ALS treatment.The aim of the study is to analyze literature (database PubMed) for potential nanotechnology usage in ALS therapy. A brief description of the state of knowledge: Nanotechnology is one of the most promising agent in many aspects of medicine, for example drug delivery, cancer therapy and wound healing. There are different kinds of nanoparticles for example gold, silver, metal-oxide, silica, lipid-based. There was one randomized clinical trial that used nanoparticles to improve bioavailability of turmeric, potential anti-inflammatory agent, in patients with ALS. This study showed that using nanoparticles is safe. Most of the recent analysis were carried out using animal models. Promising results were demonstrated in many studies.   Conclusions: The available research confirms the usefulness of nanotechnology in increasing the effectiveness of ALS treatment. Animal studies have produced surprising results. Nanoparticles can improve the absorption of drugs and bioavailability, affecting the clinical improvement of patients, which gives new possibilities and therapeutic perspectives for patients with ALS. Personalized therapy based on using molecules and profund control of such therapy can greatly improve the effectiveness of treating people with ALS.